Optimized Ultrasonic-Assisted Extraction of Aflatoxin B1 in Peanuts with Response Surface Methodology. (4th March 2017) - Yang, Jianrong; Zhao, Rui; Song, Liting; Yin, Jungang; You, Yanli; Sun, Chengfeng; Li, Yanshen
ABSTRACT: Response surface methodology was used to optimize the ultrasonic-assisted extraction conditions for aflatoxin B1 in peanuts. Box–Behnken center composite optimization was performed with factors including the ratio of sample to extractant, sonication time, and sonication temperature. Response surface methodology was used with three factors and three levels to determine the prime factors on the extraction of aflatoxin B1. High-performance liquid chromatography with fluorescence detector was used for the determination of aflatoxin B1. The optimum conditions were 1 g peanuts to 86 mL extractant, a sonication time of 7 min, and a temperature of 73°C. The mean recoveries in fortified peanuts were between 87.6 and 93.5% with an interday and intraday relative standard deviations below 10.6 and 9.8%, respectively. The developed method was accurate and precise for the determination of aflatoxin B1.